Evaluation of prognostic factors on recurrence after curative resections for hepatocellular carcinoma - Han, Jae Hyun (World J Gastroenterol, 2014)
AIM: To select appropriate patients before surgical resection for hepatocellular carcinoma (HCC), especially those with advanced tumors. METHODS: From January 2000 to December 2012, we retrospectively analyzed the medical records of 298 patients who had undergone surgical resections for HCC with curative intent at our hospital. We evaluated preoperative prognostic factors associated with histologic grade of tumor, recurrence and survival, especially the findings of pre-operative imaging studies such as positron emission tomography-computed tomography (PET-CT) and magnetic resonance imaging (MRI). And then, we established a scoring system to predict recurrence and survival after surgery dividing the patients into two groups based on a tumor size of 5 cm. RESULTS: Of the 298 patients, 129 (43.3%) developed recurrence during the follow-up period. The 5 year disease free survival and overall survival were 47.0% and 58.7% respectively. In multivariate analysis, a serum alpha-fetoprotein (AFP) level of > 100 ng/mL and a standardized uptake value (SUV) of PET-CT of > 3.5 were predictive factors for histologic grade of tumor, recurrence, and survival. Tumor size of > 5 cm and a relative enhancement ratio (RER) calculated from preoperative MRI were also significantly associated with prognosis in univariate analysis. We established a scoring system to predict prognosis using AFP, SUV, and RER. In those with tumors of > 5 cm, it showed predicted both recurrence (P = 0.005) and survival (P = 0.001). CONCLUSION: The AFP, tumor size, SUV and RER are useful for prognosis preoperatively. An accurate prediction of prognosis is possible using our scoring system in large size tumors.